Suicidal and Homicidal tendencies in an Elderly Patient with Seizures and Dementia treated with Levetiracetam [Keppra] - Sunil R Rangwani M.D, Salisu A Aikoye M.D (Academy of Social Science Journal, 2018)
Levetiracetam [Keppra] is reported to have a relative risk of 3.3 for drug induced violence. Common side effects are due an extension of its mechanism of action however the way it leads to homicidal and suicidal behaviors remain poorly understood. There have been several reports of suicidality, aggressiveness, mood lability, hostility but rarely intense homicidal ideation in patients on Keppra. We present a patient who had persistent homicidal thoughts and plan towards his wife while on Keppra. Suicidal symptoms, psychosis, aggression and hostility are significantly more common in epilepsy patients treated with Keppra and generally about 8-13.3% would have psychiatric symptoms of some sort compared to placebo groups, the incidence of aggression and hostility appears to be beyond the average incidence in patients with epilepsy. Some authors have linked aggression and hostility to genetic variation in dopaminergic activity. There is a need to further explore homicidal ideation and related factors in patients on Keppra